Creating realities across languages and modalities: Multimodal recontextualization in the translation of online news reports. (June 2020) - Altahmazi, Thulfiqar H.M.
Abstract: This paper conceptualizes the recent translation practices in online news sites as cross-lingual and multimodal recontextualization, examining their roles in creating coherent narratives with manipulative potentials. Drawing on the sociocognitive approach to context (van Dijk, 2008) and Multimodal Critical Discourse Analysis (Ledin and Machin, 2018a), the paper analyzes a corpus of 30 Arabic and English translated news reports covering ISIS news. Four strategies of multimodal recontextualization were identified; each results in different types of meaning transformation. The analysis shows that recontextualization serves different communicative functions, ranging from epistemic fine-tuning, whose aim is to provide background information necessary for inference-making; cultural adaptability, which optimizes cultural resonance for the targeted readership and enhances text authenticity; and finally normalization of ideological stances across the source and the target texts. The findings suggest that multimodal recontextualization gives rise to different contextual assumptions across source and target texts, embedding each in a different ideological narrative. Conceptualizing these texts as "meaningful wholes" with different semiotic affordances (Ledin and Machin, 2018b) elucidates how recontextualization creates manipulative narratives across languages and modalities. These narratives are created through ideological appropriation made coherent by maintaining referential, spatiotemporal and action continuity along different semiotic levels.